Implementasi Kebijakan Program Pembinaan Anak Jalanan di Kota Serang: Anak jalanan - Refa, Refa Arta Sari (NIAGARA Scientific Journal, 2024)
From the background of the problem, the researcher focused this research on how to implement the Street Children Development Program Policy in Serang City. The implementation of the street children development program is not yet optimal because there are still many street children's activities, especially in Serang City. The aim of this research is to find out how the Street Children Development Program Policy is implemented in Serang City. This research uses Van Horn and Van Metter's theory that the success of implementation is influenced by the implementation of a policy which is influenced by the characteristics of the implementing agent which includes bureaucratic structure, norms, and relationship patterns that occur in the bureaucracy in fulfilling resources, both human and human resources. non-human attitudes or tendencies of implementors include responses, understandings and value preferences held by implementors, communication between related organizations in the sense of coordination; as well as economic, social and political environmental conditions. The method used in this research is a qualitative method. Data collection techniques use interviews, observations and documentation studies. The informants for this research were the Serang City Social Service, Serang City SATPOL PP (Prajapati Police Unit), Serang City PSA (Child Social Workers), Serang City KPJ (Street Singers Community), Street Children and Street Children's Families. Testing the validity of researchers using triangulation of sources and techniques. It can be said that the research results in the Implementation of the Street Children Development Program Policy in Serang City have not run optimally.     Keywords: Street children, Implementation of the Street Children Development Program Policy in Serang City.